Hubungan Hubungan Indeks Masa Tubuh dengan Premenstrual Syndrome (PMS) - Haniyah, Siti; Dewi, Pramesti (Universitas Muhammadiyah Klaten, 2023)
PMS often occurs in teenage girls which appears with a set of symptoms both mental and physical and behavioral during the luteal phase of the menstrual cycle around 7-10 days before menstruation and disappears when menstrual blood comes out. One of the factors causing the syndrome is Body Mass Index. The aim of this study was to determine the relationship between Body Mass Index and premenstrual syndrome. The formula used in selecting respondents was total sampling with a cross-sectional approach. The assessment form used is SPAF and data analysis used Spearman rank to measure the relationship between Body Mass Index and PMS in Harapan Bangsa University. The conclusion of this study there is a relationship between BMI and PMS p: 0.00 and the relationship is quite close (0.456). Women with PMS disorders have low serotonin levels which causes early or late ovulation. This can trigger the hormones estrogen and progesterone, which cause complaints such as breast pain and bloating. At the same time, an increase in the hormone prostaglandin causes the uterus to contract which causes abdominal pain during the menstrual cycle. Keywords: Body Mass Indeks, premenstrual syndrome, female student